Early diagnosis of oesophageal cancer. - Bird-Lieberman, E; Fitzgerald, R (2009)
Squamous cell carcinoma and adenocarcinoma of the oesophagus are cancers that develop from distinct epithelial sub-types; however, they are both related to chronic inflammation of differing aetiologies. Inflammation leads to somatically inherited genetic mutations altering control of the cell cycle, DNA replication and apoptosis, which together result in autonomous and uncontrolled proliferation. These cancers have often metastasised to lymph nodes and distant organs before symptomatic presentation and therefore carry a poor prognosis. It is therefore vital to diagnose oesophageal cancer at an early stage, before the development of symptoms, when treatment can dramatically improve prognosis. Understanding the pathogenesis of these cancers is vital to guide early diagnostic strategies.